PKM Usaha Ilabulo Bakar Kecamatan Kota Selatan Provinsi Gorontalo - Rizal, Rahma; Annur, Haditsah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
The partner in the community partnership program is Usaha Ilabulo Bakar. Ilabulo is a typical snack from Gorontalo. Formerly by the kings, Ilabulo symbolizes "Totombowata" which means united. PKM program by taking independent business partners as Ilabulo Bakar business actors. Partners who until now have many competitors that are difficult to develop. Every time Ilabulo was made per night, it could only be around 500 - 600 packs. The selling price per pack is around Rp. 5,000. Related to this PKM program the proposer wants to expand his business with ilabulo products globally by online marketing. This PKM program will help partners in the form of packaging improvements, product taste and quality, brands that do not yet exist, aspects of sales using only verbal communication, as well as simple management, the concept of inventory in warehouse does not yet exist and the financial management system is still lacking manual. and online sales training (e-commerce) of ilabulo Bakar products can be made as souvenirs typical of Gorontalo.